2020
DOI: 10.3389/fmicb.2020.00523
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the Transcriptomic Response of Campylobacter coli and Campylobacter lari to Heat Stress

Abstract: Campylobacter spp. are one of the most important food-borne pathogens, which are quite susceptible to environmental or technological stressors compared to other zoonotic bacteria. This might be due to the lack of many stress response mechanisms described in other bacteria. Nevertheless, Campylobacter is able to survive in the environment and food products. Although some aspects of the heat stress response in Campylobacter jejuni are already known, information about the stress response in other Campylobacter sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 36 publications
0
16
1
Order By: Relevance
“…Since CJnc180 expression is conserved in C. jejuni and C. coli strains (Riedel et al, 2020;Dugar et al, 2013) but was not required for CJnc190 processing, its function remained unclear.…”
Section: Cjnc180 Indirectly Affects Ptmg Via Cjnc190 Antagonismmentioning
confidence: 99%
“…Since CJnc180 expression is conserved in C. jejuni and C. coli strains (Riedel et al, 2020;Dugar et al, 2013) but was not required for CJnc190 processing, its function remained unclear.…”
Section: Cjnc180 Indirectly Affects Ptmg Via Cjnc190 Antagonismmentioning
confidence: 99%
“…Variation of predicted aa sequences possibly associated with a host–generalist lifestyle of specific C. jejuni lineages were, for instance, identified for the cell division protein encoded by fts X. Recent work by Riedel et al showed that fts X transcription is downregulated in Campylobacter lari after exposure to heat stress [84], possibly indicating certain allelic variants may differ with respect to their stress response. As mentioned earlier, allelic variants may have evolved individually in both lineages (CC-45 and CC-21/CC-48), since the recombination analysis suggests a limited number of recombination events between BAPS clusters 8 and 2, 3 and 6.…”
Section: Discussionmentioning
confidence: 99%
“…E. coli, F. tularensis , Helicobacter pylori, Pseudomonas putida, Campylobacter coli , and Campylobacter lari are some of the pathogenic bacteria for which the role of ClpB in thermotolerance has been studied ( Squires et al, 1991 ; Allan et al, 1998 ; Meibom et al, 2008 ; Ito et al, 2014 ; Alam et al, 2018 , 2020 ; Riedel et al, 2020 ). F. tularensis , a highly infectious pathogen and a category A bioterrorism agent, is the etiological agent of the zoonotic disease tularemia.…”
Section: The Role Of Clpb In Stress-tolerance and Virulencementioning
confidence: 99%
“…Transcriptomic profiles of C. coli and C. lari at elevated temperatures showed enhanced gene expression of clpB and other genes encoding chaperones such as dnaK , groES , and groEL , indicating that multiple chaperones, including ClpB, play a vital role in the thermotolerance of Campylobacter spp. ( Riedel et al, 2020 ).…”
Section: The Role Of Clpb In Stress-tolerance and Virulencementioning
confidence: 99%